The role compulsory licensing in combatting counterfeit drugs in Nigeria - Umar, Musa Ibrahim (2016)
The negative implication of the existence of counterfeit to the public, government and pharmaceutical companies is one of the issue examined in this study. This leads to a question of how the concept of compulsory licensing as provided for under the relevant laws can be used to address the proliferation of counterfeit drugs in Nigeria The objective of this study is to identify how the relevant laws on compulsory licensing can be used to address the proliferation of counterfeit drugs in Nigeria. Thus, this study employed doctrinal legal method. The content analysis is used in analyzing the data collected in this research. The study found out concept of compulsory licensing has the effect of enhancing access to affordable drugs through the authorization given to other producers to manufacture the said patented drugs and this will in turn spur competition. The study also recommends the government to issue compulsory licensing over patented drugs in order to assist the public to get of affordable and quality drugs in Nigeria